The Impact of the Novel A untuk Amanda on Readers’ Psychology: A Receptive-Pragmatic Literary Psychology Study - Lenie Nuraeni Pujayantie; H Halimah; S Sumiyadi (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
This study aims to identify and analyze the psychological impact experienced by readers after reading the novel A untuk Amanda, as well as to reveal the narrative factors that influence their psychological responses. This study employed a mixed methods approach with an explanatory sequential design and a receptive-pragmatic literary psychology approach. Data were collected through questionnaires distributed to 30 respondents who had read the novel, then analyzed using descriptive quantitative methods and interpreted qualitatively. The results showed that most readers experienced excessive anxiety (63.3%) and sadness (33.3%) after reading the novel. The factor that most influenced readers’ psychological condition was the characters’ behavior (66.7%), indicating the significant role of characterization in building readers’ emotional engagement. Although most respondents reported no long-term psychological impact, some readers demonstrated personal reflection, such as an increased awareness that success is not everything. This study confirms that literary fiction can evoke emotional responses, encourage psychological reflection, and reinforce the relevance of literary psychology approaches that focus on readers’ experiences.